AKIBAT HUKUM ATAS PERSEROAN TERBATAS YANG PERUBAHAN ANGGARAN DASARNYA TIDAK DIDAFTARKAN PADA KEMENTRIAN HUKUM DAN HAK ASASI MANUSIA (Putusan Mahkamah Agung Nomor 183/Pdt.G/2014/PN.JAKSEL) - SYARIFAH RIZKA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. BISMAR NASUTION2. SUNARMI3. T. KEIZERINA DEVI A A limited liability company is obliged to make amendment deed of articles of association for every amendment made. The amendment of the articles of association of a company is made before a notary. It is in line with what is mentioned in Article 19 of the Law No. 40/2007 on Limited Liability Company stating that “amendment of articles of association is determined by RUPS (Shareholders’ General Meeting) and the events concerning the amendment has to be clearly mentioned in the summon to RUPS.” As the articles of the association of the Limited Liability Company is validated, registered and published, it is not only binding the founders of the company, shareholders and managers, but also all parties intending to make transactions with it.Keywords: Limited Liability, Article of Association, Notarial Deed